Respectable citizens - shady practices : the economic morality of the middle classes - Farrall, Stephen; Karstedt, Susanne (Oxford : Oxford University Press, 2020)
This text seeks to explore a previously neglected aspect of crime in modern society - namely those crimes committed by otherwise 'respectable' citizens in the market arena. It outlines the contours of the contemporary moral economy, and asks, is a 'predatory society' emerging from the central sphere of consumption?
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 23, 2020).
Keywords: White collar crimes; Middle class; Economics -- Moral and ethical aspects; True Crime; Social services & welfare, criminology